Framing stigma as an avoidable social harm that widens inequality. Issue 2 (March 2023) - Addison, Michelle
This article discusses the social harms arising out of stigma experienced by people who use drugs (PWUD), and how stigmatisation compromises 'human flourishing' and constrains 'life choices'. Drawing on Wellcome Trust qualitative research using in-depth, semi-structured interview data ( N = 24) with people who use heroin, crack cocaine, spice and amphetamine, this article firstly provides insight into how stigma is operationalised relationally between people via a lens of class talk and drug use predicated on normative ideas of 'valued personhood'. Secondly, it turns to how stigma is weaponised in social relations to keep people 'down', and thirdly, it shows how stigma is internalised as blame and shame and felt deeply 'under the skin' as 'ugly feelings'. Findings from the study show that stigma harms mental health, inhibits access to services, increases feelings of isolation, and corrodes a person's sense of self-worth as a valued human being. These relentless negotiations of stigma are painful, exhausting and damaging for PWUD, culminating in, as I argue, everyday acts of social harm that come to be normalised.